Tariff Bindings and the Dynamic Formation of Preferential Trade Agreements - James Lake; Moïse Nken; Halis Murat Yildiz (Center for Economic Studies and ifo Institute (CESifo), 2019)
We show that multilateral tariff binding liberalization substantially impacts the nature and extent of Preferential Trade Agreement (PTA) formation. First, it shapes the nature of forces constraining expansion of Free Trade Agreements (FTAs). The constraining force is a free riding incentive of FTA non-members under relatively high bindings but an exclusion incentive of FTA members under relatively low bindings. Second, multilateral tariff binding liberalization shapes the role played by PTAs in the attainment of global free trade. Initially, tariff binding liberalization leads to Custom Union (CU) formation in equilibrium but in a way that undermines the pursuit of global free trade. However, further tariff binding liberalization leads to FTA formation in equilibrium and in a way that facilitates the attainment of global free trade. Our theoretical analysis also has implications regarding recent empirical discussions over the relative merits of FTAs versus CUs.
Keywords: C72; F12; F13; 330; tariff bindings; preferential trade agreement; free trade agreement; customs union; global free trade; dynamic